2009
DOI: 10.1007/s11548-009-0365-3
|View full text |Cite
|
Sign up to set email alerts
|

Illustrative visualization of 3D planning models for augmented reality in liver surgery

Abstract: Purpose: Augmented Reality (AR) obtains increasing acceptance in the operating room. However, a meaningful augmentation of the surgical view with a 3D visualization of planning data which allows reliable comparisons of distances and spatial relations is still an open request. Methods: We introduce methods for intraoperative visualization of 3D planning models which extend illustrative rendering and AR techniques. We aim to reduce visual complexity of 3D planning models and accentuate spatial relations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(42 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…Bugüne kadar artırılmış gerçeklik araçları; reklam, pazarlama, mühendislik, müze, mimarlık, inşaat, eğlence, sağlık alanları ve askeri alanlarda kullanılmıştır (Azuma, 1997;Barfield, 2015;Hansen, Wieferich, Ritter, Rieder ve Petigen, 2010;Feiner, 2002;Karatay, 2015;Küçük, Kapakin ve Göktaş, 2015;Sayımer ve Küçüksaraç, 2015;Uğur ve Ceylan, 2014;Koşan, 2014). Ancak mobil cihazların (masaüstü ve diz üstü bilgisayarlar, taşınabilir cihaz, akıllı telefonlar vs.) kullanımının artmasıyla birlikte artırılmış gerçeklik uygulamaları (AGU) eğitimde de kullanılmaya başlanmıştır (Billinghurst, 2002;Johnson, Smith, Levine ve Hywood, 2010;Uluyol ve Eryılmaz, 2014).…”
Section: Introductionunclassified
“…Bugüne kadar artırılmış gerçeklik araçları; reklam, pazarlama, mühendislik, müze, mimarlık, inşaat, eğlence, sağlık alanları ve askeri alanlarda kullanılmıştır (Azuma, 1997;Barfield, 2015;Hansen, Wieferich, Ritter, Rieder ve Petigen, 2010;Feiner, 2002;Karatay, 2015;Küçük, Kapakin ve Göktaş, 2015;Sayımer ve Küçüksaraç, 2015;Uğur ve Ceylan, 2014;Koşan, 2014). Ancak mobil cihazların (masaüstü ve diz üstü bilgisayarlar, taşınabilir cihaz, akıllı telefonlar vs.) kullanımının artmasıyla birlikte artırılmış gerçeklik uygulamaları (AGU) eğitimde de kullanılmaya başlanmıştır (Billinghurst, 2002;Johnson, Smith, Levine ve Hywood, 2010;Uluyol ve Eryılmaz, 2014).…”
Section: Introductionunclassified
“…Therefore, the development of intraoperative navigation surgery followed by simulation had been promising [22,23,24,25]. However, there have not been many studies on AR-based NS applicable for clinical practice by facing the obstacle of organ deformity [8,26,27,28,29,30,31,32,33]. Although many investigations using current engineering technologies and mathematical algorithms have been reported to overcome problems associated with organ deformity, most systems are not practical because of complicated methods and insufficient [28,29,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Depth information could be recovered in future applications by coding it into the models being projected as suggested for example by Hansen et al [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, authors such as Hansen et al [1] and Sugimoto et al [2] have reported on the disadvantages of displaying navigation data on a separate screen. Hansen concluded that mental fusion of planning models with the current surgical view was error-prone and that it frequently resulted in distracting comparisons during the intervention that consumed an unacceptable amount of time.…”
Section: Introductionmentioning
confidence: 99%